Impact of CD40 (rs1883832) and CD40L (rs1126535) gene variants on laryngeal cancer susceptibility and their association with serum biomarker levels of sCD40 and sCD40L. - Alper Gümüş; Dilara Sönmez; Şeyda Demirkol; Mehmet Tolgahan Hakan; Ayşegül Verim; Yusufhan Süoğlu; İlhan Yaylım; Arzu Ergen (PLoS ONE)
Introduction The most prevalent head and neck cancer type is laryngeal cancer. Laryngeal cancer susceptibility is increased by a combination of genetic variables and environmental factors. Genetic predispositions that influence the functioning of the immune system can affect tumor development. Our study investigates the impact of alterations in CD40 (rs1883832) and CD40L (rs1126535) genes and the levels of their proteins on the development of laryngeal cancer. Materials and methods The PCR-RFLP method was used for genotyping SNPs in 96 patients with laryngeal cancer and 127 healthy individuals. Additionally, ELISA was utilized to measure circulating levels of sCD40 and sCD40L. Results We identified a significant difference in the genotype distribution of CD40 (rs1883832) between laryngeal cancer patients and healthy individuals (p = 0.05). The C allele was dominant, and the CC genotype was more frequently observed in patients with laryngeal cancer (OR: 2.34, 95% CI: 0.98-5.54). In contrast, no statistically significant difference in the genotypes of CD40L (rs1126535) was detected between laryngeal cancer patients and the control group (p = 0.12). Additionally, no significant differences in serum sCD40 or sCD40L levels were observed between the groups (p = 0.48 and p = 0.15, respectively). However, a moderate positive correlation was found between sCD40 and sCD40L levels in the laryngeal cancer group (r = 0.52, p<0.01), a relationship that was not observed in the control group. Discussion According to the current findings, it is suggested that the CD40 (rs1883832) gene variation found in patients may indicate an individual's susceptibility to developing laryngeal cancer. On the other hand, CD40L (rs1126535) seems to not play a significant role. While serum sCD40 and sCD40L levels did not show significant differences between patients and controls, the correlation in cancer patients suggests that these markers may be relevant in tumor progression. Further research is required to clarify the functional implications of these genetic variants and their potential use as biomarkers for laryngeal cancer.